2018
DOI: 10.1097/ijg.0000000000000841
|View full text |Cite
|
Sign up to set email alerts
|

Meibomian Gland Performance in Glaucomatous Patients With Long-term Instillation of IOP-lowering Medications

Abstract: Patients with a higher BAG agents had more unstable tear films and more severe MG dropout. Therefore, MG disease should be particularly observed in patients with glaucoma following a higher BAG regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 33 publications
3
14
1
1
Order By: Relevance
“…It is well known that different hypotensive drops present diverse local and systemic side effects, and some of them affect blood pressure [7], which in turn could influence the ocular surface temperature [20]. A decrease in the temperature of the ocular surface may lead to a decrease in the quality of the tear film since secretions from the glands such as the meibonium glands are negatively affected by lower temperatures [21]. The participants in this study used a wide variety of glaucoma medications.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that different hypotensive drops present diverse local and systemic side effects, and some of them affect blood pressure [7], which in turn could influence the ocular surface temperature [20]. A decrease in the temperature of the ocular surface may lead to a decrease in the quality of the tear film since secretions from the glands such as the meibonium glands are negatively affected by lower temperatures [21]. The participants in this study used a wide variety of glaucoma medications.…”
Section: Resultsmentioning
confidence: 99%
“…Again, the study showed a significant difference in Marx line and breakup time according to the presence of meibomian gland dysfunction between the cases and controls 19 . Cho and colleagues reported that patients with glaucoma had significantly worse meibum quality, thinner lipid layer thickness, and lower meibomian gland secretion compared to healthy controls 20 …”
Section: Resultsmentioning
confidence: 90%
“…A notable limitation in this approach is that long-term use of topical anti-glaucoma medications increases the risk of developing ocular surface diseases [15]. Several previous studies have shown that the high incidence of dry eye, as well as the deterioration of ocular parameters and meibomian gland dysfunction (MGD) in glaucoma patients using IOP-lowering eyedrops is associated with the use of topical anti-glaucoma medications [610]. Previously, we also reported that glaucoma patients using topical anti-glaucoma medications showed deterioration of ocular surface status, including reduction in the thickness of the tear lipid layer [11].…”
Section: Introductionmentioning
confidence: 99%
“…Meibomian gland (MG) condition in glaucoma patients is related to the behaviors involved in medication use, such as frequency and duration, as well as the type of preservative and active ingredient in the medication [6,7,9,10,12]. Among several active ingredients used as topical anti-glaucoma medications, prostaglandin analogues (PGAs) are known to be associated with development of MGD [8,9,1315].…”
Section: Introductionmentioning
confidence: 99%